The Impact of Infrastructure and Accessibility on the Satisfaction Level of Paragliding Sport Tourism Tourists at Salena Hill - Nurlina Ambo; Humaedi Humaedi; Moh Wahyu Firmansyah; Andi Sultan Brilin; Susandi Eka Wahyudi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to determine the impact of infrastructure and accessibility on the level of satisfaction of paragliding sport tourism tourists at Bukit Salena, Palu City, Central Sulawesi. Infrastructure and accessibility are important factors in the development of tourist destinations because they affect the comfort, safety, and experience of tourists during tourism activities. Bukit Salena as one of the sport tourism destinations has great potential for development, so it is necessary to evaluate the condition of the available infrastructure and accessibility. This study uses a quantitative approach with a survey method. The sampling technique used accidental sampling, with a total of 20 respondents who have paragliding activities at Bukit Salena. Data collection was carried out through distributing questionnaires using a Likert scale, observation, and documentation. Data were analyzed using descriptive statistical analysis in the form of percentages to describe the level of tourist satisfaction with infrastructure and accessibility. The results showed that the level of tourist satisfaction with infrastructure and accessibility at Bukit Salena was in the very good category. A total of 13 respondents (65%) gave a very good rating, 6 respondents (30%) gave a good rating, and 1 respondent (5%) gave a poor rating. These results indicate that the existing infrastructure and accessibility provide a sense of safety and comfort, and support tourist activities during paragliding at Salena Hill. However, improvements are still needed in several aspects, such as the quality of the road leading to the site, the completeness of public facilities, and the maintenance of supporting infrastructure to continuously enhance tourist satisfaction.